2020
DOI: 10.3390/vetsci7030124
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Findings in Testes from Apparently Healthy Drones of Apis mellifera ligustica

Abstract: It is well known that factors acting on the decrease of population of honeybees, can act on the male and female reproductive system, compromising the fertility of queens and drones. While there are many studies on female fertility, only a few studies have focused on male fertility and the possible alterations of the reproductive system. The testes of 25 samples of adult drones of Apis mellifera ligustica were analyzed by histopathology using an innovative histological processing technique and the alterations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Power et al ( Power et al 2020 ) recently published an investigation of histopathological changes in testes of 25 free-flying healthy drones, the age of which was estimated according to whole-body mass ( Metz and Tarpy 2019 ). Based on microscopic evaluation, 17/25 drones had normal testicular parenchyma with germ cells within follicular cells and spermatodesms in tubular lumens which correspond to histological Stages I and II, respectively, described in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Power et al ( Power et al 2020 ) recently published an investigation of histopathological changes in testes of 25 free-flying healthy drones, the age of which was estimated according to whole-body mass ( Metz and Tarpy 2019 ). Based on microscopic evaluation, 17/25 drones had normal testicular parenchyma with germ cells within follicular cells and spermatodesms in tubular lumens which correspond to histological Stages I and II, respectively, described in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed degeneration and necrosis of follicular and germ cells within seminiferous (testicular) tubule of 5/25 drones and delayed or incomplete maturation of germ cells in 2/25 drones. Interestingly, Power et al ( Power et al 2020 ) also indicated that an experimental histopathological study describing testicular changes during sexual maturation of drones was lacking. The current study fills this gap, and the detailed histological description of testicular changes will enable differentiation of normal atrophic processes occurring during sexual maturation from pathological processes described by Power et al ( Power et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power et al found an innovative histological processing technique to analyse healthy drones of A. mellifera ligustica. The new approach can detect testes alterations, such as degenerated seminiferous tubules [ 21 ].…”
mentioning
confidence: 99%
“…Samples were processed as previously described [ 69 ]. Briefly, honeybees were individually injected with 10 μL of 10% buffered formalin and then stored for 24 h in 50 mL tubes containing the same fixative.…”
Section: Methodsmentioning
confidence: 99%